Opioid Prescriptions for Female Pelvic Reconstructive Surgery Patients Before and After Implementation of Tennessee State Legislation. Issue 12 (December 2020) - Samimi, Parisa; Panza, Joseph; Heft, Jessica; Wang, Li; Adam, Rony
Abstract : Objectives: Limited data exist regarding the impact of state legislation on opioid-prescribing patterns, particularly in states with the highest opioid-prescribing rates in the nation. Our primary objective was to examine the change in the amount of opioid morphine equivalents (OMEs) prescribed at discharge to patients undergoing female pelvic reconstructive surgery after the implementation of state legislation created in response to the opioid crisis. Methods: At our institution, state legislation went into effect on July 1, 2018, implementing limitations on OMEs prescribed to patients. This retrospective cohort study examines all adult women undergoing female pelvic reconstructive surgery from January 1, 2018, to December 31, 2018. The study compares prescribing practices 6 months before and 6 months after the state law was enacted. Results: In total, 346 patients met inclusion criteria. The 2 groups had similar demographics. Surgical procedures were well distributed, with 52% of cases occurring in the first 6 months of the calendar year. At the time of discharge, 324 (96.7%) patients received an opioid prescription, with an overall average of 197 OMEs. After the implementation of state legislation on July 1, 2018, the amount of OMEs prescribed at discharge significantly decreased, from a median of 210 mg (interquartile range, 150–225) to 150 mg (interquartile range 135–225; P = 0.02). Conclusions: State legislation was associated with a significant decrease in prescribed OMEs at the time of discharge in patients undergoing female pelvic reconstructive surgery. These results support ongoing legislative efforts to address the current opioid crisis. Abstract : Legislative efforts enacted in response to the opioid epidemic are effective in reducing the amount prescribed to women undergoing pelvic surgery.